SPECTROSCOPIC AND THERMAL ANALYSES OFTHE INHIBITORY MECHANISM OF OKANIN ON XANTHINE OXIDASE - LI, Meng-Rong; LIU, Mu-Xin; LIU, Wei; HE, Rui; JIANG, Shan-Bin; LI, Shen-Qiang (Studia Universitatis Babeș-Bolyai Chemia, 2025)
Okanin was identified as a xanthine oxidase inhibitor, and for the first time, the thermodynamic parameters of the interaction—including entropy change (ΔS), enthalpy change (ΔH), and Gibbs free energy (ΔG)—were calculated by combining fluorescence spectrometry and differential thermal scanning. It can be inferred that there exists a hydrogen bond between okanin and XO, with the van der Waals force being the predominant intermolecular force between them. Nuclear Magnetic Resonance Hydrogen Spectroscopy (1H-NMR) not only confirmed the presence of hydrogen bonding but also provided initial predictions of the specific binding location of the inhibitor and enzyme. Three-dimensional and synchronous fluorescence demonstrated that okanin induces structural modifications in the enzyme, leading to inhibition. Molecular docking directly revealed the binding pattern between inhibitor and enzyme, which aligned with the aforementioned experiments. The findings indicated that inhibitors were competitively bound to the enzyme’s active site primarily through intermolecular forces such as hydrogen bonding, conjugation, and van der Waals forces. These interactions facilitate the formation of a stable intermediate, inducing structural changes in the enzyme, and enhancing the inhibitory ability of okanin. Antioxidant experiments showed that okanin further inhibits the generation of O2- free radicals by simultaneously promoting the reduction of XO molecules and suppressing the production of uric acid. Hence, okanin shows promise as a novel natural product that inhibits the activity of xanthine oxidase, making it highly significant to investigate its potential anti-gout properties.